Development and validation of sex-associated markers using whole-genome re-sequencing in frog Quasipaa spinosa - Zhang, Liaoruilin; Li, Juan; Li, Xiang; He, Jinrong; Zhou, Jie; Hou, Jinliang; Liu, Yulu; Zhang, Lei; Huang, Yanfei; Li, Hong; Liao, Xiaolin; Liu, Xinhua; et al. (Frontiers in Genetics, 2025)
The development of sex markers is crucial for addressing monosexual breeding in aquaculture species and for identifying traits that are sexually inherited, especially for elucidating the mechanisms of sex determination in amphibians. In aquaculture, comprehending sex determination is especially vital because the market value of animal products frequently depends on their sex. Quasipaa spinosa (Anura, Dicroglossidea) is a valuable frog species in the aquaculture industry of China and southeast Asia, yet there exists limited genomic information regarding this organism. Current data indicates that the adoption of all-male breeding techniques in Q. spinosa could substantially benefit the Chinese aquaculture industry, both by augmenting its economic prospects and by ensuring the effectiveness of wildlife reintroduction efforts. The growth rate, adult size, disease resistance, and other traits of male Q. spinosa surpass those of females, making the development of all-male breeding a significant focus in the Q. spinosa aquaculture industry. Therefore, it is imperative to establish a marker specific to males. In this research, we used the male Q. spinosa genome as reference and performed whole-genome resequencing on 30 males and 30 females. Subsequently, we exhibited evident sexual differentiation on chromosome 3 and primers were designed for PCR detection of the identified candidate male INDEL loci. Ultimately, two sex-associated INDELs that could be effectively detected were obtained and validated on the samples collected from the remaining three locations, thereby confirming the robustness of these two INDELs for sex identification in Q. spinosa.